2018
DOI: 10.1159/000492840
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylases Induces K+ Channel Remodeling and Action Potential Prolongation in HL-1 Atrial Cardiomyocytes

Abstract: Background/Aims: Cardiac arrhythmias are triggered by environmental stimuli that may modulate expression of cardiac ion channels. Underlying epigenetic regulation of cardiac electrophysiology remains incompletely understood. Histone deacetylases (HDACs) control gene expression and cardiac integrity. We hypothesized that class I/II HDACs transcriptionally regulate ion channel expression and determine action potential duration (APD) in cardiac myocytes. Methods: Global class I/II HDAC inhibition was achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This is in line with an unaltered H4-acetylation in atria from WT VPA mice, which might point to a possible long-term compensatory mechanism because H4-acetylation was increased acutely in WT atria by VPA. Recently, Lugenbiel et al 70 reported AP prolongation in HL-1 cardiomyocytes after 12-hour treatment with the pan-HDAC inhibitor TSA. Such an effect seems not to be present after prolonged treatment with VPA in mice, which might depend on VPAs HDAC inhibitory profile or efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with an unaltered H4-acetylation in atria from WT VPA mice, which might point to a possible long-term compensatory mechanism because H4-acetylation was increased acutely in WT atria by VPA. Recently, Lugenbiel et al 70 reported AP prolongation in HL-1 cardiomyocytes after 12-hour treatment with the pan-HDAC inhibitor TSA. Such an effect seems not to be present after prolonged treatment with VPA in mice, which might depend on VPAs HDAC inhibitory profile or efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were subjected to electrical stimulation as reported using the C-Pace EP system (IonOptix, Westwood, MA, USA). 25 The cells were stimulated with 10 V/10 ms pulses at 5 Hz stimulation rate. Following rapid electrical stimulation for 24 h, cell viability was visually assessed by microscopic examination and TUNEL assays.…”
Section: Methodsmentioning
confidence: 99%
“…Protein immunodetection was performed using sodium dodecyl sulfate (SDS) gel electrophoresis and Western blotting as described previously. 25 Equal amounts of protein were separated on 10% SDS polyacrylamide gels and transferred onto polyvinylidene difluoride membranes. Membranes were blocked with 5% milk in PBS-T for 2 hours at room temperature and developed using primary antibodies directed against K Ca 2.1 (1:1000, APC-039), K Ca 2.2 (1:1000, APC-028) and K Ca 2.3 (1:1000, APC-025, all from Alomone Lab, Jerusalem, Israel).…”
Section: Methodsmentioning
confidence: 99%
“…Gelatin-/fibronectin-coated six-well dishes were seeded with 4-5 × 10 6 HL-1 cells. Cells were ≥90% confluent after 24 h incubation and subjected to electrical stimulation as described (Lugenbiel et al, 2018) using the C-Pace EP system (IonOptix). Stimulation was performed with 10 V/10 ms pulses at 4 Hz rates.…”
Section: Electrical Stimulation Of Hl-1 Cellsmentioning
confidence: 99%
“…To date, histone deacetylase (HDAC) effects on cardiac K + currents have been almost exclusively investigated using broad range inhibitors. In vitro, APD prolongation and reduced expression of K + channels were observed in atrial cardiomyocytes after application of broad‐spectrum inhibitors of HDACs (Lugenbiel et al, 2018). Furthermore, inhibition of class I HDACs resulted in AF suppression in animal models (Seki et al, 2016; Skibsbye et al, 2018, Scholz et al 2019).…”
Section: Introductionmentioning
confidence: 99%